Robust Statistical Procedures For Testing The Equality Of Central Tendency Parameters Under Skewed Distributions [QA276.A12 S531 2005 f rb]. - Soaad Syed Yahaya, Sharipah (2005)
Kajian ini menyelidik kesan ralat Jenis I dan kuasa keatas dua jenis kaedah teguh. Kaedah pertama dikenali sebagai statistik S1 yang julung kalinya diselidik oleh Babu et al. (1999). This study examined the effect of Type I error and power on two types of robust methods. The first method is known as the S1 statistic, which was first studied by Babu et al. (1999).